Panorama of Researches on Satisfaction in Teaching Work in the Cognitive Social Perspective (Research, Society and Development, 2020)
The job satisfaction of teachers has been associated with the affective reactions of these professionals in relation to the teaching function. This study aims to build an overview of research on teacher job satisfaction, conducting a systematic review. Articles published from 2000 to 2016 were collected in the databases of CAPES - periodicals and Scielo. The searches resulted in 36 sources for analysis. It was noted, from the results of the surveyed articles, that the studies sought to investigate the occurrence of a relationship between satisfaction in teaching work with some variables, such as: self-efficacy, collective effectiveness, emotional exhaustion, stress, among others. The relationship between these variables has been an important focus of studies on the referred construct from the Social Cognitive Theory. In addition, it was found to be important that more research on the topic of satisfaction in teaching work be carried out in order that more articles are published in the area.